Modern Business Ethics from a Business Philosophy View: Etika Bisnis Modern dalam Pandangan Filsafat Bisnis - Farhani, Fithrah; Imran, Zulfi; Syarifuddin, Syarifuddin (ITScience (Information Technology and Science), 2024)
Business ethics is a knowledge of the ideal procedures for regulating and managing a business that takes into account norms and morality that apply universally. Ethics is also a part of philosophy that discusses values, norms and morality rationally and intensively. The method used is a qualitative method using a literature study approach. The data sources used are secondary data sources obtained through analysis of literature, books and journals or other sources. This research aims to explore business ethics from the perspective of business philosophy. In running a business, it is important to uphold moral principles and justice in decision making. Modern companies have a responsibility to contribute positively to society and the environment, which is known as corporate social responsibility (CSR). In addition, the business philosophy view of modern business ethics adheres to the principle of mutual benefit, where all parties involved in business received posiyive benefits. Modern business ethics is not only about compliance with rules, but also about applying moral values and responsibilityin every aspect of business. By applying modern business ethics, you can achieve sustainable success and provide benefits for all parties involved.